2018
DOI: 10.1096/fj.201800655r
|View full text |Cite
|
Sign up to set email alerts
|

Differential functional selectivity and downstream signaling bias of ghrelin receptor antagonists and inverse agonists

Abstract: The ghrelin receptor [growth hormone secretagogue receptor (GHSR)‐1a] represents a promising pharmacologic target for the treatment of metabolic disorders, including obesity and cachexia, via central appetite modulation. The GHSR‐1a has a complex pharmacology, highlighted by G‐protein–dependent and—independent downstream signaling pathways and high basal constitutive activity. The functional selectivity and signaling bias of many GHSR‐1a–specific ligands has not been fully characterized. In this study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 81 publications
1
37
0
2
Order By: Relevance
“…74 Indeed, it is likely that the interaction of these synthetic ligands with GHSR involves a variety of partially biased effects. 74,77 Moreover, we cannot rule out that handling-induced stress affected our observations to some extent because central infusions per se slightly decreased 2-hour HF intake in our experiments. Thus, the current observations should be interpreted cautiously with these considerations in mind.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…74 Indeed, it is likely that the interaction of these synthetic ligands with GHSR involves a variety of partially biased effects. 74,77 Moreover, we cannot rule out that handling-induced stress affected our observations to some extent because central infusions per se slightly decreased 2-hour HF intake in our experiments. Thus, the current observations should be interpreted cautiously with these considerations in mind.…”
Section: Discussionmentioning
confidence: 75%
“…Given the complexity of the biology of GHSR, a selective pharmacological manipulation of specific features of the receptor has been shown to be challenging . Indeed, it is likely that the interaction of these synthetic ligands with GHSR involves a variety of partially biased effects . Moreover, we cannot rule out that handling‐induced stress affected our observations to some extent because central infusions per se slightly decreased 2‐hour HF intake in our experiments.…”
Section: Discussionmentioning
confidence: 87%
“…For example, pancreatic studies using [ d ‐Lys 3 ]‐GHRP‐6 concluded that it was an inverse agonist against GHSR1a Gα i signalling, although this does not align with recent studies reporting that ghrelin‐GHSR signalling in the pancreas is coupled to Gα q , nor more recent studies demonstrating that [ d ‐Lys 3 ]‐GHRP‐6 functions as a biased antagonist against GHSR1a β‐arrestin signalling . Numerous compounds have been used to investigate GHSR1a signalling (eg, [ d ‐Lys 3 ]‐GHRP‐6, substance P, JMV2959) and these careful studies highlight the inherent complexities of GHSR1a signalling, enabling a revised understanding regarding drugs, originally assumed to be antagonists or inverse agonists, functioning instead as biased antagonists or partial agonists for specific downstream signalling cascades . Thus, the nuances of pharmacological interference with GHSR1a must be taken into account when interpreting past and designing future experiments.…”
Section: Mechanism Of Action Of Ghrelin On Insulin Secretionmentioning
confidence: 97%
“…Studies of GHSR1a signalling in δ‐cells did not examine constitutive activity and mostly found that ghrelin signalling acted downstream via the Gα q pathway . However, downstream GHSR1a activity may occur through Gα q , Gα 1/3 , Gα o , Gα i or β‐arrestin signalling and these differential downstream signalling cascades have been implicated for the diverse roles of ghrelin . Although the bulk of this work has been carried out in transfected cells or lipid discs, evidence also exists in vivo .…”
Section: Mechanism Of Action Of Ghrelin On Insulin Secretionmentioning
confidence: 99%
“…Estos comportamientos duales no son excepcionales ya que muchos ligandos sintéticos de GHSR tampoco funcionan estrictamente como agonistas, antagonistas o agonistas inversos sino que poseen características mixtas dependiendo de las vías que activan o inhiben, evidenciando la complejidad del funcionamiento de GHSR (Ramirez et al, 2018).…”
Section: Ghsr: El Receptor De Ghrelinaunclassified